Implementación de prototipo a escala de secador mecánico de café pergamino en la finca Las Palmas vereda San Antonio del Pescado (Garzón – Huila) (2021)
Traditionally, coffee is dried on cement floors with direct exposure to the sun occupying large areas, later indoor systems such as helba-houses and canopies were created, these are followed by mechanized equipment, however, they involve the use of raw materials for combustion and a high consumption of electrical energy and labor is incurred. This project proposes the construction of a scale prototype of a mechanical wet parchment coffee dryer to evaluate the preservation of its organoleptic properties, ensuring the reduction of energy consumption and the emission of polluting particles. The methodology to be developed is experimental with an operational prototype where the design phases proposed by (Parra Coronado, Roa Mejia, Oliveros Tascón, & Saenz Uribe, 2017) will be applied, which are: analysis of the problem and conceptual design, the step to This step includes the stages of construction, assembly, start-up, validation and results of the prototype elaborated in the Las Palmas farm in the San Antonio del Pesa village (Garzón - Huila). Once the validation tests have been completed, it is determined that it is easy to operate, does not use raw materials to generate heat and the economic performance of drying can be corroborated by means of the mathematical formulas set out. It is emphasized that the design is part of an investigative process that promotes future phases to improve its physical characteristics and greater drying capacity.